Collective Vibrational Strong Coupling Effects on Molecular Vibrational Relaxation and Energy Transfer: Numerical Insights via Cavity Molecular Dynamics Simulations. Issue 28 (1st June 2021) - Li, Tao E.; Nitzan, Abraham; Subotnik, Joseph E.
Abstract: For a small fraction of hot CO2 molecules immersed in a liquid‐phase CO2 thermal bath, classical cavity molecular dynamics simulations show that forming collective vibrational strong coupling (VSC) between the C=O asymmetric stretch of CO2 molecules and a cavity mode accelerates hot‐molecule relaxation. This acceleration stems from the fact that polaritons can be transiently excited during the nonequilibrium process, which facilitates intermolecular vibrational energy transfer. The VSC effects on these rates 1) resonantly depend on the cavity mode detuning, 2) cooperatively depend on Rabi splitting, and 3) collectively scale with the number of hot molecules. For larger cavity volumes, the average VSC effect per molecule can remain meaningful for up to N ≈10 4 molecules forming VSC. Moreover, the transiently excited lower polariton prefers to relax by transferring its energy to the tail of the molecular energy distribution rather than distributing it equally to all thermal molecules. As far as the parameter dependence is concerned, the vibrational relaxation data presented here appear analogous to VSC catalysis in Fabry–Pérot microcavities. Abstract : We performed cavity molecular dynamics simulations and showed that, under vibrational strong coupling conditions, vibrational relaxation and energy transfer from hot to thermal molecules can be accelerated relative to that outside a cavity due to polariton‐accelerated intermolecular vibrational energy transfer.